Immunity to malaria: more questions than answers. - Langhorne, J; Ndungu, F; Sponaas, A; Marsh, K (2008)
Malaria is one of the main health problems facing developing countries today. At present, preventative and treatment strategies are continuously hampered by the issues of the ever-emerging parasite resistance to newly introduced drugs, considerable costs and logistical problems. The main hope for changing this situation would be the development of effective malaria vaccines. An important part of this process is understanding the mechanisms of naturally acquired immunity to malaria. This review will highlight key aspects of immunity to malaria, about which surprisingly little is known and which will prove critical in the search for effective malaria vaccines.